2021
DOI: 10.3389/fcell.2021.719720
|View full text |Cite
|
Sign up to set email alerts
|

Protein Lactylation Critically Regulates Energy Metabolism in the Protozoan Parasite Trypanosoma brucei

Abstract: Lysine lactylation has been recognized as a novel post-translational modification occurring on histones. However, lactylation in non-histone proteins, especially in proteins of early branching organisms, is not well understood. Energy metabolism and the histone repertoire in the early diverging protozoan parasite Trypanosoma brucei, the causative agent of African trypanosomiasis, markedly diverge from those of conventional eukaryotes. Here, we present the first exhaustive proteome-wide investigation of lactyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 70 publications
4
40
0
Order By: Relevance
“…Our studies revealed that lactylated proteins were distributed in diverse compartments (especially the mitochondria) and were significantly enriched in energy metabolism processes such as oxidative phosphorylation, glyoxylate and dicarboxylate metabolism, glycolysis/gluconeogenesis, and TCA cycle (Figure 2, Figure S2 and S3). Our results are also in line with previous findings in Trypanosoma brucei and rice, where lactylation is important for gene transcription and central carbon metabolism [48,49]. We therefore focused on the link between lactylation and the processes of energy metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Our studies revealed that lactylated proteins were distributed in diverse compartments (especially the mitochondria) and were significantly enriched in energy metabolism processes such as oxidative phosphorylation, glyoxylate and dicarboxylate metabolism, glycolysis/gluconeogenesis, and TCA cycle (Figure 2, Figure S2 and S3). Our results are also in line with previous findings in Trypanosoma brucei and rice, where lactylation is important for gene transcription and central carbon metabolism [48,49]. We therefore focused on the link between lactylation and the processes of energy metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Histone sites modified through lactylation have previously been identified in several eukaryotic species [ 3 , 5 8 ] and were found to directly activate gene expression [ 3 ]. In the present study, a total of 20 Kla sites on T. gondii canonical and variant histones were identified, including five sites on H2B (K37, K47, K70, K77 and K99), four sites on H3 (K23, K27, K56 and K122), three sites on H2A (K5, K137 and K142) and one site on H4 (K31), H2A1 (K73) and H2AX (K127) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). Sequence alignment analysis suggests that the Kla site on either H2A.zK137 or H2BK99 in T. gondii was also present in humans [ 3 ] and T. brucei [ 8 ]. Lactylation on H3K23, H3K27 and H4K31 in T. gondii is also conserved in human cells at the same site [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations